Subclinical Hypothyroidism Predicted Adverse Cardiovascular Events in Patients with Ejection Fraction Preserved Heart Failure - Tan Q; Chen M; Yang H; Guo Y; Zou X (Dove Medical Press, 2024)
Qiang Tan, Ming Chen, Hongmei Yang, Yao Guo, Xiaoyi Zou Department of Cardiology, Qinhuangdao First Hospital, Hebei Medical University, Qinhuangdao, Hebei Province, People's Republic of ChinaCorrespondence: Qiang Tan, Department of Cardiology, Qinhuangdao First Hospital, Hebei Medical University, Qinhuangdao, Hebei Province, People's Republic of China, Email qhdtanqiang@aliyun.comBackground: Subclinical hypothyroidism (SH) increases the risk of cardiovascular events, however the influence of SH on prognosis of ejection fraction preserved heart failure (HFpEF) is not fully understood.Methods: In this prospective observational study, patients with HFpEF were divided into euthyroidism group (n = 413) and SH group (n = 79). Patients were followed up for at least 30 months to examine the association between SH and cardiovascular events in patients with HFpEF. The primary end point was composite cardiovascular events (cardiovascular death and re-hospitalization). The patients underwent flow-mediated dilation (FMD) measurement by ultrasound in order to value endothelial function.Results: The rate of composite cardiovascular events was higher in SH group than in euthyroidism group (54.49% and 26.36%, respectively; p < 0.001). The higher risk of cardiovascular events in SH group was primarily due to a higher risk of re-hospitalization compared to euthyroidism group (45.56% and 20.58%, respectively; p < 0.001). The rate of cardiovascular death was higher in SH group than in euthyroidism group (13.92% and 5.81%, respectively; p = 0.017). Cox proportional hazards regression showed that SH (hazard ratios [HR] 1.921, 95% confidence interval [CI] 1.139- 3.240), level of TSH (HR 1.025, 95% CI 1.010- 1.054), age (HR 1.017, 95% CI 1.002- 1.034), LVEF (HR 0.975, 95% CI 0.953- 0.996), atrial fibrillation (HR 1.581, 95% CI 1.083- 2.307), eGFR (HR 0.987, 95% CI 0.978- 0.997), and NYHA cardiac function (HR 2.342, 95% CI 1.649- 3.326) were independent predictors of cardiovascular events in patients with HFpEF (all P < 0.05).Conclusion: Subclinical hypothyroidism was associated with increased cardiovascular events and death in patients with HFpEF.Keywords: subclinical hypothyroidism, ejection fraction preserved heart failure, endothelial function, flow-mediated dilation, cardiovascular events